2011
DOI: 10.1364/oe.19.014067
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of optical emission from laser-induced plasmas by combined spatial and magnetic confinement

Abstract: He, X. N.; Li, C. M.; Zhou, Y. S.; Cai, Z. X.; Zeng, X. Y.; and Lu, Yongfeng, "Enhancement of optical emission from laser-induced plasmas by combined spatial and magnetic confinement" (2011 Abstract: To enhance optical emission in laser-induced breakdown spectroscopy, both a pair of permanent magnets and an aluminum hemispherical cavity (diameter: 11.1 mm) were used simultaneously to magnetically and spatially confine plasmas produced by a KrF excimer laser in air from pure metal and alloyed samples. High enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(43 citation statements)
references
References 24 publications
1
41
1
Order By: Relevance
“…Popov et al reported the confinement effect of plasmas created in a small capped cylindrical chamber whose size was 4 mm by 4 mm, improved the limit of detection (LOD) by two to five times for different elements [24,25]. Our previous research also showed the enhancement of plasmas confined with an aluminum hemispherical cavity, resulting in an enhancement factor of 12 for Mn lines in a substrate with a low Mn concentration [26,27]. Wang et al fabricated a polytetrafluoroethylene (PTFE) plate of 1.5 mm thick with a diameter of 3 mm to regularize coal plasma.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Popov et al reported the confinement effect of plasmas created in a small capped cylindrical chamber whose size was 4 mm by 4 mm, improved the limit of detection (LOD) by two to five times for different elements [24,25]. Our previous research also showed the enhancement of plasmas confined with an aluminum hemispherical cavity, resulting in an enhancement factor of 12 for Mn lines in a substrate with a low Mn concentration [26,27]. Wang et al fabricated a polytetrafluoroethylene (PTFE) plate of 1.5 mm thick with a diameter of 3 mm to regularize coal plasma.…”
Section: Introductionmentioning
confidence: 75%
“…The plasma was compressed and become uniform; therefore, the spectral line intensity was enhanced. As a result, the accuracy of quantitative analysis was improved [27,28].…”
Section: Calibration Curves For V Cr and Mnmentioning
confidence: 99%
“…Early investigations focused on measurements of plasma parameters and in the identification of magnetic field induced kinetic effects on plasma behavior. [6][7][8] Later, several investigations on laser plasma dynamics in sub-Tesla static magnetic fields have been reported, aiming to improve plasma confinement in pulsed laser deposition (PLD) processes, 9,10 to enhance plasma emission in laser induced breakdown spectroscopy (LIBS), [11][12][13] to increase the ion yield and beam current in laser ion sources (LIS), 14 or to get insight in interpreting data related to astrophysical observations, 15,16 among others. In this context we report on a series of experiments aiming to unveil further details of the interaction between the laser produced plasma and a static axial magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Guo Lianbo [4],etc., for example, the support vector machine algorithm assisted laser induced breakdown spectroscopy research of qualitative identification technology for a variety of plastic. Although he has performed well in such studies, but did not involve the classification of scrap metal in.…”
Section: Introductionmentioning
confidence: 99%